Analisis Potensi Sampah di Kuantan Singingi untuk Pembangkit Listrik Tenaga Sampah (PLTSa) Landfill Gas (LFG) - Boy Ihsan; Dicky Pangindra; Iswadi Hasyim Rosma (Universitas Merdeka Malang, 2025)
Waste Power Plant (PLTSa) is one of the solutions to overcome waste problems and as electricity supply. This study analyzes the technical and economic feasibility of building a PLTSa at the Muaro Sentajo Landfill, Kuantan Singingi Regency, which uses the sanitary landfill method. The organic waste produces landfill gas (LFG), especially methane, which can be used as fuel for power generation. The estimated LFG content was calculated using the U.S. Environmental Protection Agency model and Landfill Gas Emmisions Model (LandGEM) software. The results show that by the end of the operation period, the landfill can produce 2,966,400 m³ of methane gas capable of operating a power plant with output of 2.39 MW. The analysis shows that the project is financially feasible, with a Net Present Value (NPV) of Rp13.8 billion, Benefit-Cost Ratio (BCR) of 1,1648, Internal Rate of Return (IRR) of 14.2%, and Payback Period of 11 years 8.3 months